Factor Analysis in Predicting Non-Medical Employees Turnover Intention - Darmawan, Akhmad (Cita konsultindo, 2025)
This research examines how quality of work life (QWL) and work-family conflict (WFC) affect turnover intention (TI) in private hospitals, and how organisational commitment (OC) mediates these effects. The aim is to explore how QWL and WFC affect TI and to assess the mediating effect of OC. Understanding these relationships is crucial as high turnover disrupts hospital operations, increases costs, and impacts patient care quality. A non-probability saturation sampling strategy was utilised with 280 non-medical workers. SEM-PLS was used to analyse Likert scale questionnaires for validity and reliability and hypothesis testing using structural model assessment. WFC increases TI, whereas QWL and OC decrease it. OC mediates the negative link between QWL and TI and the positive association between WFC and TI. Hospital management should enhance QWL and minimize WFC to reduce turnover. Policies supporting work-life balance, employee recognition, and career growth are recommended. This research shows that organisational commitment mediates the effects of QWL and WFC on TI, providing insights for employee well-being and retention tactics.